Efektivitas Edukasi Pretest-Posttest dalam Meningkatkan Kemampuan Kognitif Kritis Konsep Halal dan Thayyib pada Siswa SMA Muhammadiyah 1 Yogjakarta - Nita Rusdiana; Endang Sunariyanti; Nuraini Nuraini; Anni Rohimah; Lingga Lingga (Journal of Empowerment Community, 2026)
The implementation of the Halal Product Guarantee Law No. 33 of 2014 in Indonesia requires a comprehensive public understanding, not only on food but also medicines and cosmetics. This activity aims to measure and improve the level of knowledge and critical thinking skills of MUHI High School students regarding the concepts of halal and thayyib. The activity uses a pretest-posttest design involving grade XI. The evaluation instrument consists of six questions representing Bloom's six cognitive levels (knowledge to evaluation). The instrument is proven valid (R Count > 0.444) and has acceptable reliability (Cronbach's Alpha = 0.685). Educational interventions focus on Halal Critical Points. The average overall score has increased significantly, from 72.1% (pretest) to 94.2% (posttest). The highest percentage increases were seen at the Knowledge (C1) and Understanding (C2) levels, which previously had the lowest initial scores (48.6% and 59.5%), respectively, showing increases of 40.6% and 32.4%. The Application (C3) level achieved a perfect 100% score on the posttest. This model was effective in transforming initial theoretical gaps into practical and critical mastery of the material. Significant improvements across all cognitive levels confirm the success of the structured intervention in preparing students to become intelligent and critical halal consumers.